2017
DOI: 10.1155/2017/6903817
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and Phytochemical, Antioxidative, and Antifungal Activities ofPergularia tomentosaL.

Abstract: Crude extracts from a medicinal Tunisian plant, Pergularia tomentosa L., were the investigated natural material. Butanolic extract of roots analyzed with IR spectra revealed the presence of hydroxyl, alcoholic, and carboxylic groups and sugars units. Analysis of some secondary metabolites, total phenolic, flavonoids, flavonols, and procyanidins, was performed using different solvents following the increased gradient of polarity. Fruits and leaves contained the highest amounts of all these compounds. Antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…Although there was no significant difference between the cytotoxicity of Pergularia tomentosa and Priploca aphylla extracts on Leishmania and Vero cell line, but it is clear that in each extract concentration, cytotoxicity effect of the extracts on Vero cell line is lower than toxicity on Leishmania promastigotes, this is promising to continue the study of these plants to find the effective metabolites on Leishmania and other trypanosomatid parasites. Our findings about the effectiveness of these plants extracts on Leishmania major are consistent with the experiences of the local traditional therapists and also are in accordance with the results of studies conducted by several researcher such as, Savita G, Imen L, Khalid A, Joseph A, Jamshed I, that have been reported the potent antimicrobial activity of Pergularia tomentosa and Priploca aphylla [17][18][19]33 . The local traditional therapists successfully use the diluted white latex of Pergularia tomentosa and decoction of the leaves and stems of Priploca aphylla to treat cutaneous form of leishmaniasis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although there was no significant difference between the cytotoxicity of Pergularia tomentosa and Priploca aphylla extracts on Leishmania and Vero cell line, but it is clear that in each extract concentration, cytotoxicity effect of the extracts on Vero cell line is lower than toxicity on Leishmania promastigotes, this is promising to continue the study of these plants to find the effective metabolites on Leishmania and other trypanosomatid parasites. Our findings about the effectiveness of these plants extracts on Leishmania major are consistent with the experiences of the local traditional therapists and also are in accordance with the results of studies conducted by several researcher such as, Savita G, Imen L, Khalid A, Joseph A, Jamshed I, that have been reported the potent antimicrobial activity of Pergularia tomentosa and Priploca aphylla [17][18][19]33 . The local traditional therapists successfully use the diluted white latex of Pergularia tomentosa and decoction of the leaves and stems of Priploca aphylla to treat cutaneous form of leishmaniasis.…”
Section: Discussionsupporting
confidence: 90%
“…Imen L. and his colleagues in their study showed that the P. tomentosa stems and fruits aqueous extracts exhibit antifungal activity against Fusarium oxysporum f. sp. lycopersici which could become an alternative to synthetic fungicide drugs 17 . Also Results from Khalid A. and his colleagues study showed that the ethanolic extract of P. tomentosa caused a higher mortality of Aedes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, bioactive molecules extracted from MAPs have revealed anti-inflammatory properties through TNF- α inhibition and in vitro decrease of nitric oxide generation [ 13 ]. Natural antioxidants might be more beneficial than synthetic ones, with the latter causing potential health side effects during long intake periods [ 14 ].…”
Section: Medicinal and Aromatic Plantsmentioning
confidence: 99%
“…Protective products originated from natural substances mainly from plants as alternative to synthetic fungicides is the spotlight issue nowadays [ 92 ]. Natural antimicrobial products are inexpensive and they have a potential for implementation in fungal pathogenic systems [ 93 ].…”
Section: Biological Activities Of Fraxinus Planmentioning
confidence: 99%